Effects of tualang honey on paraquat intoxication in rats - Peng, Tang Suk (2016)
Paraquat (PQ) is an herbicide widely used in the world and has been postulated to exert its toxic effects via the production of various reactive oxygen species causing subsequent oxidative damage at key cellular components. Tualang honey (TH) has been reported to possess good antioxidant properties and may help ameliorate the oxidative damages in case of PQ poisoning. Therefore, the main objectives of this study were to evaluate the possible protective effect of TH in acute (study 1) and subacute (study 2) PQ toxicities in rats. Male Sprague-Dawley rats aged eight weeks old were used. In study 1, selected oral doses of PQ and TH were 225 mg/kg and 0.2 g/kg, respectively. The effects of single and multiple TH treatments on PQintoxicated rats were then investigated: single TH treatment groups received TH at 0.5 (PQ + TH0.5h), 2 (PQ + TH2h) or 6 (PQ + TH6h) hours following PQ administration; multiple TH treatment groups received TH at 0.5, 2 and 6 hours (PQ + THtrp) or further daily treatment for next six days (PQ + TH7d) following PQ administration, respectively (n = 6 per group). The survival time of each rat was recorded until day 28 before sacrifice. Although treatment with TH did not improve the survival rate of PQ-intoxicated rats, the median survival time of rats which received multiple TH treatments was significantly longer when compared to group PQ + TH6h. Furthermore, TH treatment improved the histological outcome of PQintoxicated rats particularly in the lungs, thus suggesting the potential role of honey in delaying the toxic effects of PQ. In study 2, the protective effect of TH on PQinduced oxidative stress in rats’ midbrain and lung regions were investigated (n= 15 per group). The rats were orally treated with distilled water (Groups N & PQ, 2 mL/kg/day), TH (Groups TH & PQ + TH, 1.0 g/kg/day) or ubiquinol (Group PQ + QH, 0.2 g/kg/day) throughout the experimental period. Two weeks after the respective treatments, the rats were administered with saline (Groups N & TH; 1 mL/kg/week, i.p) or PQ (10 mg/kg/week, i.p.; Groups PQ, PQ + TH and PQ + QH) once a week for four consecutive weeks. The animals were then sacrificed a week following the final injection of saline or PQ. Serum urea was significantly lower in groups which received TH (TH and PQ + TH) or ubiquinol (PQ + QH). Serum creatinine was markedly reduced in group PQ + TH as well, when compared to controls (N and TH). Significantly lower levels of ALT were observed in groups TH and PQ + TH when compared to group PQ. These findings suggest that TH treatment may have some beneficial effects on the kidney and liver’s function. Following fourweekly PQ-administration, the midbrain GPx activity was significantly reduced when compared to healthy control (N). PQ-induced dopaminergic neuronal damage was demonstrated by a significant reduction in the number of tyrosine hydroxylaseimmunopositive neurons in the midbrain substantia nigra pars compacta while in the lungs, marked reduction in the activities of SOD and GST were observed in group PQ when compared to the control group. Treatment with TH ameliorates the toxic effects seen in the midbrain and lungs with comparable effects to ubiquinol, the control drug used in study 2. These findings suggest that pre-treatment with TH showed some protective effects against subacute PQ toxicities. It is plausible that the protective effects of TH are conferred by its antioxidant properties.